1971
DOI: 10.1159/000230585
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cutaneous Histamine Sensitivity in Children with Pertussis

Abstract: Enhanced sensitivity to histamine of children with pertussis has been the basis for speculation regarding similarities of receptor sites among the limited species of mammals said to be hypersensitive, and regarding the desirability of eliminating histamine-sensitizing factor from conventional pertussis vaccines. However, significantly enhanced sensitivity to i.e. injected histamine could not be demonstrated in a group of 6 children with pertussis compared to 4 controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…To summarize, histamine sensitization in mice in response to B. pertussis infection was first described over 50 years ago (606). Subsequently, histamine sensitization was studied by many investigators, but only five studies involving humans were carried out (269,486,501,561,574,576,618,622,625,686,701,801). In a 1948 study, Parfentjev and Goodline found that mice injected intraperitoneally with a pertussis vaccine subsequently became hypersensitive to histamine challenge; 2 mg of histamine had similar lethality in sensitized (previously vaccinated) mice as did 50 mg in unvaccinated mice (606).…”
Section: Virulence Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…To summarize, histamine sensitization in mice in response to B. pertussis infection was first described over 50 years ago (606). Subsequently, histamine sensitization was studied by many investigators, but only five studies involving humans were carried out (269,486,501,561,574,576,618,622,625,686,701,801). In a 1948 study, Parfentjev and Goodline found that mice injected intraperitoneally with a pertussis vaccine subsequently became hypersensitive to histamine challenge; 2 mg of histamine had similar lethality in sensitized (previously vaccinated) mice as did 50 mg in unvaccinated mice (606).…”
Section: Virulence Determinantsmentioning
confidence: 99%
“…In three controlled studies in children, histamine sensitization could not be demonstrated in association with B. pertussis infection or following vaccination (269,501,618). In the most recent study, Gifford et al compared skin test sensitivity to histamine in DT-and DTP-immunized children and found no significant difference in wheal size between the two groups (269).…”
Section: Virulence Determinantsmentioning
confidence: 99%
“…Nevertheless there is little doubt that, during an infection with B.pertussis, PT gains access to the circulation of the patient, because lymphocytosis (absolute or relative) is a well-recognised diagnostic sign (Walker et al, 1981) in the disease and can reasonably be attributed to this toxin. Regarding HSF activity, there is a report (Sanyal, 1960), but also a denial (Pieroni et al, 1971), of histaminesensitisation in children with pertussis. From the IAP activity of PT, it might be expected that plasma insulin would be elevated in pertussis; but no supporting data have yet been published.…”
Section: Introductionmentioning
confidence: 99%